Implementation of quality management for clinical bacteriology in low-resource settings. (July 2017) - Barbé, B.; Yansouni, C.P.; Affolabi, D.; Jacobs, J.
Abstract: Background: The declining trend of malaria and the recent prioritization of containment of antimicrobial resistance have created a momentum to implement clinical bacteriology in low-resource settings. Successful implementation relies on guidance by a quality management system (QMS). Over the past decade international initiatives were launched towards implementation of QMS in HIV/AIDS, tuberculosis and malaria. Aims: To describe the progress towards accreditation of medical laboratories and to identify the challenges and best practices for implementation of QMS in clinical bacteriology in low-resource settings. Sources: Published literature, online reports and websites related to the implementation of laboratory QMS, accreditation of medical laboratories and initiatives for containment of antimicrobial resistance. Content: Apart from the limitations of infrastructure, equipment, consumables and staff, QMS are challenged with the complexity of clinical bacteriology and the healthcare context in low-resource settings (small-scale laboratories, attitudes and perception of staff, absence of laboratory information systems). Likewise, most international initiatives addressing laboratory health strengthening have focused on public health and outbreak management rather than on hospital based patient care. Best practices to implement quality-assured clinical bacteriology in low-resource settings include alignment with national regulations and public health reference laboratories, participating in external quality assurance programmes, support from the hospital's management, starting with attainable projects, conducting error review and daily bench-side supervision, looking for locally adapted solutions, stimulating ownership and extending existing training programmes to clinical bacteriology. Implications: The implementation of QMS in clinical bacteriology in hospital settings will ultimately boost a culture of quality to all sectors of healthcare in low-resource settings.